2015
DOI: 10.1021/acs.jafc.5b01011
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Extraction of Phenolic Compounds from Almond Skin Byproducts (Prunus amygdalus): A Multivariate Analysis Approach

Abstract: 26A microwave-assisted extraction (MAE) procedure to isolate phenolic compounds from 27 almond skin by-products was optimized. A three-level, three-factor Box-Behnken 28 design was used to evaluate the effect of almond skin weight, microwave power and 29 irradiation time on total phenolic content (TPC) and antioxidant activity (DPPH). 30Almond skin weight was the most important parameter on the studied responses. The 31 best extraction was achieved using 4 g, 60 s, 100 W and 60 mL of 70% (v/v) ethanol. 32 TPC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 36 publications
9
78
0
1
Order By: Relevance
“…The most usual procedure includes the use of Box-Behnken experimental designs (BBD) or central composite designs (CCD). Good results were reported for the extraction of target compounds, such as antioxidants from almond skin [52], peanut skin [53] and batata leaves [54], highlighting the potential of MAE as a promising extraction method for pectins.…”
Section: Extraction Methods For Pectins: New Trends For the Revalorizmentioning
confidence: 99%
“…The most usual procedure includes the use of Box-Behnken experimental designs (BBD) or central composite designs (CCD). Good results were reported for the extraction of target compounds, such as antioxidants from almond skin [52], peanut skin [53] and batata leaves [54], highlighting the potential of MAE as a promising extraction method for pectins.…”
Section: Extraction Methods For Pectins: New Trends For the Revalorizmentioning
confidence: 99%
“…It must also be noted that when quantifying phenolic compounds with GC, there is sometimes a requirement for chemical modification, such as transformation to more volatile derivatives (Khoddami et al, 2013). studies have demonstrated the efficacy of this technique in the extraction of phenolics, although from different sources, including rice grains and almond skin by-products (Setyaningsih et al, 2015;Valdés et al, 2015). The success of this technique in extracting phenolic compounds means it could be a useful method to isolate phenolic compounds from rapeseed meal, but further optimisation and validation are necessary.…”
Section: Characterisation Strategies For Rapeseed Meal Phenolicsmentioning
confidence: 99%
“…In the last years, novel sustainable extraction techniques such as Ultrasound-Assisted Extraction (UAE), Microwave-Assisted Extraction (MAE), Supercritical CO2 Extraction, Supercritical Fluid Extraction (SFE), Accelerated Solvent Extraction (ASE) and Pressurized Hot Water Extraction (PHWE) or Subcritical Water Extraction (SWE) which allow to reduce extraction time and solvent consumption, increase nutraceutical yield and improve plant extract quality (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Subcritical water extraction is called green technology because it is a rapid and efficient recovery method as compared with conventional extraction methods.…”
Section: Introductionmentioning
confidence: 99%